Effectiveness of Pokea (Batissa violaceae celebensis Martens, 1897) Shells in Reducing Hexavalent Chromium - Atmasari, Kica; Rasyid, Sri Anggarini; Azizi Jayadipraja, Erwin (Waluya The International Science of Health Journal, 2024)
Introduction: Preliminary data obtained showed that the Hexavalent Chromium (VI) content found in the Lasolo River had a concentration of 0.3 mg/l which exceeded the quality standard. Pokea shellfish (Batissa violaceae celebensis Martens, 1897) is an adsorbent used to reduce hexavalent chromium levels in water. Method: The methodology used is experimental with a quantitative approach. This study used variations in adsorbent mass and contact time, with variations in adsorbent mass of 2.5 with variations in contact time for 30 minutes, 60 minutes, and 120 minutes. Result: Adsorption effectiveness of Hexavalent Chromium (VI) using Pokea Shell powder (Batissa Violaceae Celebensis Martens, 1897) with a mass of 2.5 g with a variation of contact time of 30 minutes with a decrease of 16.53%. Adsorption effectiveness of Hexavalent Chromium (VI) using Pokea Shell powder (Batissa Violaceae Celebensis Martens, 1897) with a mass of 2.5 g with a variation of contact time of 60 minutes with a decrease of 21.37%. Adsorption effectiveness of Hexavalent Chromium (VI) using Pokea Shell powder (Batissa Violaceae Celebensis Martens, 1897) with a mass of 2.5 g with a variation of contact time of 120 minutes with a decrease of 33.46%. Conclusion: The conclusion in this journal The most effective in reducing Hexavalent Chromium (VI) was using Pokea Shell powder (Batissa Violaceae Celebensis Martens, 1897) with a mass of 2.5 g with a variation of contact time of 120 minutes with a reduction of 33.46%.